Analisis Peluang Perpindahan Konsumen dengan Metode Rantai Markov pada 3 Kuliner Baso Di Galuh Mas Telukjambe Karawang - Muhammad Harun; Agustian Suseno (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2021)
The meatballs culinary in area Galuh Mas Karawang is a bustling area and is often visited by the public. The research sample consisted of 167 respondents who were only visitors and direct customers in March 2021. The research method was in the form of a questionnaire and analysis using the Markov chain. The results showed that in the 10th period in November 2021, it reached a balance point with the percentage for Baso Ambon, which was 54%, in the second place, Baso Sopo Nyono was 25% and the lowest was for Baso Malang, 21%. The purpose of the study was to determine the magnitude of the consumer opportunities for the three meatballs culinary MSMEs there are Baso Ambon, Baso Malang and Baso Sopo Nyono, and predict the opportunities for their transfer in the coming period to the three meatball dishes.